2014
DOI: 10.1088/0268-1242/29/4/043001
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of ZnO: a review

Abstract: Due to the unique set of properties possessed by ZnO, thin films of ZnO have received more and more interest in the last 20 years as a potential material for applications such as thin-film transistors, light-emitting diodes and gas sensors. At the same time, the increasingly stringent requirements of the microelectronics industry, among other factors, have led to a dramatic increase in the use of atomic layer deposition (ALD) technique in various thin-film applications. During this time, the research on ALD-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
312
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 371 publications
(333 citation statements)
references
References 295 publications
19
312
1
1
Order By: Relevance
“…This suggests that more O2 2− or VO defects are generated with longer O2 plasma times while the formation of both the stoichiometric Zn-O bond and the O-H bond are suppressed. Hall measurements revealed that all ZnO films deposited in this work were n-type, in correspondence with other reported works [12]. It is believed this n-type conductivity originates from the presence of the defects and impurities in the ZnO crystal.…”
Section: Zno Thin Filmssupporting
confidence: 91%
See 3 more Smart Citations
“…This suggests that more O2 2− or VO defects are generated with longer O2 plasma times while the formation of both the stoichiometric Zn-O bond and the O-H bond are suppressed. Hall measurements revealed that all ZnO films deposited in this work were n-type, in correspondence with other reported works [12]. It is believed this n-type conductivity originates from the presence of the defects and impurities in the ZnO crystal.…”
Section: Zno Thin Filmssupporting
confidence: 91%
“…0.90 to 0.94 was observed which corresponds well with other reported ZnO films deposited by ALD with plasma treatment [16]. In addition, all films exhibit relatively good stoichiometry compared to the ZnO films deposited from thermal ALD [12,16]. This is due to the fact that O2 plasma is much more reactive than H2O [12].…”
Section: Zno Thin Filmssupporting
confidence: 87%
See 2 more Smart Citations
“…The number of the small peaks was two less than the number of oxide layers (N-2, N=number of repetition cycles), as expected. 27 The N-2 trend was clearly seen in superlattice structures having 4-7 oxide layers but not anymore with 8. The XRR patterns are displayed in Fig.…”
Section: Resultsmentioning
confidence: 97%